Changes of Fecal Bifidobacterium Species in Adult Patients with Hepatitis B Virus-Induced Chronic Liver Disease - Xu, Min; Wang, Baohong; Fu, Yiqi; Chen, Yanfei; Yang, Fengling; Lu, Haifeng; Chen, Yunbo; Xu, Jiali; Li, Lanjuan (Microbial ecology, 2012)
The beneficial effects of Bifidobacteria on health have been widely accepted. Patients with chronic liver disease have varying degrees of intestinal microflora imbalance with a decrease of total Bifidobacterial counts. Since different properties have been attributed to different Bifidobacterium species and there is no information available for the detailed changes in the genus Bifidobacterium in patients with chronic liver disease heretofore, it is meaningful to investigate the structure of this bacterium at the species level in these patients. The aim of this study was to characterize the composition of intestinal Bifidobacterium in patients with hepatitis B virus-induced chronic liver disease. Nested-PCR-based denaturing gradient gel electrophoresis (PCR-DGGE), clone library, and real-time quantitative PCR were performed on the fecal samples of 16 patients with chronic hepatitis B (CHB patients), 16 patients with hepatitis B virus-related cirrhosis (HBV cirrhotics), and 15 healthy subjects (Controls). Though there was no significant difference in the diversity among the three groups (P= 0.196), Bifidobacterium dentium seems to be specifically enhanced in patients as the PCR-DGGE profiles showed, which was further validated by clone library and real-time quantitative PCR. In contrast to the B. dentium, Bifidobacterium catenulatum/Bifidobacterium pseudocatenulatum were detected less frequently in the predominant profile and by quantitative PCR in HBV cirrhotics than in the controls, and the level of this species was also significantly different between these two groups (P= 0.023). Although having no quantitative difference among the three groups, Bifidobacterium longum was less commonly detected in HBV cirrhotics than in CHB patients and Controls by quantitative PCR (P= 0.011). Thus, the composition of intestinal Bifidobacterium was deeply altered in CHB and HBV cirrhotic patients with a shift from beneficial species to opportunistic pathogens. The results provide further insights into the dysbiosis of the intestinal microbiota in patients with hepatitis B virusinduced chronic liver disease and might potentially serve as guidance for the probiotics interventions of these diseases.